Diagnostic Accuracy of Fetal Middle Cerebral Artery (MCA) Peak Systolic Velocity (PSV) In Prediction of Neonatal Anemia in Rhesus Alloimmunisation - Rabia Younas; Umme Kalsoom; Mahjabeen Yaseen; Anum Yousaf shah; Faran Nasrullah; Irum Qaisar (KARACHI MEDICAL AND DENTAL COLLEGE, 2023)
ABSTRACT Objectives: To assess the diagnostic accuracy of Middle Cerebral Artery (MCA) Peak Systolic Velocity (PSV) in Prediction of Neonatal Anemia keeping neonatal hemoglobin (Hb) at birth as gold standard.   Methods :A Cross sectional validation study conducted at Radiology department o from 26th November 2019 till 26th May 2020.A total of 125 pregnant women between 32-35 weeks were included through non probability consecutive sampling. The PSV was measured in the MCA closest to the transducer. An average of three readings was taken. An MCA-PSV of > 1.5 multiples of median (MoM) was taken as positive. The neonatal blood was sent for hemoglobin estimation soon after birth to the hospital pathology laboratory. The result of MoM was noted and compared with neonatal hemoglobin. Results: Out of 125 pregnant women between 32-35 weeks, the mean age of the patients was 25.81 ± 5.82 years. Most of the women were multiparous that is 67 out of 125 (53.6%), and primiparous were 58 that constituted 46.4% of the total. 34.4% patients were anemic according to middle cerebral artery peak systolic velocity (MCA-PSV) while hematology laboratory reported 32.8% of neonates as anemic according to cut off hemoglobin of less than 13.5 gm/ dl. Sensitivity, specificity, PPV, NPV and accuracy of the MCA-PSV in detecting the anemia was 90.2%, 92.9%, 86%, 95.1% and 92% respectively.   Conclusion: MCA- PSV Doppler is a useful modality for diagnosis of fetal anemia, although the primary means should be neonatal hemoglobin estimation at birth. Keywords: Color Doppler ultrasound, MCA- PSV, Neonatal Hemoglobin